From Headlines to Public Awareness: A Media Discourse Analysis of The Los Angeles 2025 Wildfire - Dwi Savandha, Septien; Amelia, Amelia; Dwi Putri Pramesti, Ginna Novarianti (Institut Manajemen Wiyata Indonesia, 2025)
The 2025 Los Angeles wildfires reflect the serious challenges of disaster management in the era of climate change. Increasing extreme temperatures and droughts have exacerbated the frequency and intensity of fires, resulting in significant damage to the environment, public health, and local economies. This study aims to evaluate the effectiveness of firefighting resources and identify community responses to the disaster. The methods used are content analysis of news from mass media and observation of community responses through social media. Samples were taken purposively from relevant news and posts during the fire incident. The results showed that more than 8,500 firefighters were deployed, utilizing somewhat effective air and ground extinguishing strategies, which increased fire control from 14% to 24% within a few days. On the other hand, 205,000 residents were successfully evacuated, indicating a high level of public awareness and preparedness. Approximately 65% of residents were also actively involved in fire prevention efforts, with social media serving as the primary means of disseminating information. In conclusion, the success of fire control is greatly influenced by resource coordination and community participation. This research makes a significant contribution to the development of more responsive and collaborative fire mitigation strategies in the future, particularly in the context of growing risks associated with climate change.